If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 = 4x + 16 Reorder the terms: 12 + 2x = 4x + 16 Reorder the terms: 12 + 2x = 16 + 4x Solving 12 + 2x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + 2x + -4x = 16 + 4x + -4x Combine like terms: 2x + -4x = -2x 12 + -2x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -2x = 16 + 0 12 + -2x = 16 Add '-12' to each side of the equation. 12 + -12 + -2x = 16 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 16 + -12 -2x = 16 + -12 Combine like terms: 16 + -12 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| (30x^2-42x)/x=(-20x^2-7x)/x | | 39-2x=48+x | | X^2=90-2 | | x+(.0825)x=18 | | 16x^2+5x-21=0 | | 5x/3-1/4=x/2 | | x+x(.0875)=18 | | 2/4=18/72 | | 2.7×3.2/4.8= | | 3-2*(x-2)=x-18 | | 3x-7x=49-5x | | 2x+y=0.5y | | 12-4K+2m=0 | | x-7+x+3=2x-17 | | (2x-3)+(5x-9)=0 | | 63=4w+29 | | 3x+5=3(X+1)+2 | | 4sen^2-3=0 | | 3x^2-7x-20000=0 | | x^2+2x=450 | | 10x^2-22x+5=0 | | -9(f-7)=18 | | 7x+4y+7z-2x+5z-8y= | | 6y-3x+5x-6y-2x+7y= | | 10d+8=6d+32 | | -2x/7=10 | | x^2-3xy=y^2+13 | | 9(x+3)=-9(x+3) | | -55=-19-2x | | lnx+ln(x-6)+ln(x-3)=ln(4x) | | 3-3*6+2=r | | 9(6x-3)=6(9x-6) |